Konsep Analogi Ferdinand De Saussure (Telaah Kajian Linguistik Barat) - Tsaniya Ruchamain (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Linguistics play an important role in the development of a alnguage. Analogy, which is one of the studies in linguistics, has a direct influence on the development of language rules. Many linguistic’s figure discuss analogy in general and specifically a language, one of which is the French father of modern linguistics, Ferdinand de Saussure. This study aimsto reveal the notions and concepts of analogy according to Ferdinand. The method used by the writer is descriptive method. From this study, it is known that the concepts of western analogy and arabic analogy have many similarities. The difference is in the learning method and its implementation.